Curriculum Quality and Personal Resources as Predictors of Subjective Employability among TESOL Students and Graduates in Cambodia - Hornmann Banh (Journal of Mathematics Instruction, Social Research and Opinion, 2026)
This study examines how TESOL program quality and personal resources predict graduates’ perceived employability in one program in the Cambodian private university. A cross-sectional survey of TESOL students and recent graduates (n = 263) measured five curriculum factors and four personal factors against five indicators of subjective employability. Correlation and regression analyses revealed that all curriculum and personal factors were positively associated with self-perceived employability. Practice-intensive curriculum features (teaching practicum, peer teaching) and personal resources (teaching self-efficacy, outcome expectations) showed particularly strong links with employability outcomes. In a combined model, personal factors – especially work adaptation, social capital, and outcome expectations – accounted for substantially more variance in employability perceptions than curriculum factors. Because the data are cross-sectional, self-reported, and drawn from a single institution, the findings indicate associations rather than causation and may not generalize to other TESOL programs or contexts. The findings suggest that while high-quality training contributes to graduates’ career readiness, their adaptability, professional networks, and future-oriented outlook ultimately play a more decisive role in how employable they feel. The study recommends enhancing authentic teaching practice, career guidance, and networking opportunities in TESOL programs to improve graduate employability.